ARUS KAS UNTUK MENDETEKSI MANIPULASI AKTIVITAS RIIL DAN DAMPAKNYA TERHADAP KINERJA PASAR - Elsa Imelda; Melina Djauhari (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2021)
The purpose of this research is to analyze the real activity manipulation can be detected through operating cash flow and its impact to market performance. This research was using 92 data from consumer goods companies listed on theIDXduring the period of 2017-2019. This research also using purposive sampling method and processed using data panel analysis by EViews (Econometrical Views) version 10 software. The results of this study indicates that real activity manipulation can be detected through operating cash flow and real activity manipulation has a significant positive effect on market performance. The implications of this study are investors are expected to be able conduct a more in-depth evaluation of the market performance of a company before making an investment decision and this research can be a reference or consideration for company managers who wish to carry out earning management, especially through real activitiy manipulation.